The poynting effect in soft composite materials - Tan, Jasmine Wei Ling (2015)
The Poynting effect in soft homogenous cylinders under pure torsion as well as the inversion and perversion of soft homogenous cylinders under pure axial loading are studied. In the context of this project, the Poynting effect is described as the tendency for the cylinder to elongate or contract in axial direction when torsion is applied. Inversion refers to the point at which the elongation of the cylinder in the axial direct reaches a maximum point when under pure axial loading. Perversion refers to the point at which a change from elongation to contraction in the axial direction occurs under pure axial loading. The net change in the homogenous cylinder under torsion due to the Poynting is also studied. The project focuses on the theoretical aspects of the cylinder under pure torsion and pure axial loading through the application of second-order elasticity and Lagrangian equilibrium equations. Soft materials in the human body can exhibit the Poynting effect as well as inversion and perversion. Thus, soft material within cardiac papillary muscle analyzed along with soft gels and metals. Attention is given to the second-order and third order elastic constants that give rise to contraction in the axial direction or a negative Poynting effect when under torsion. It is found that a negative Poynting effect is typically seen in material with positive third-order elastic constants. Results also suggest a correlation between the negative Poynting effect and the inversion and perversion of the cylinder under pure torsion and pure axial loading respectively. It is also found that net change volume of the homogenous cylinder under pure torsion relates to the radial displacement associated with the Poynting effect.